ANALISA PENGELASAN MILD STEEL (ST.42) DENGAN PROSES SMAW, FCAW DAN SAW DITINJAU DARI SEGI KEKUATAN DAN NILAI EKONOMIS - Hadi, Eko Sasmito (Department of Naval Architecture - Diponegoro University, 2009)
In this era, the growth of welding technology is very fast, especially in newship building and repairing ship construction. The welding work often rise the delaying which cause of lost of cost, time and material consumables. Developing of speed and efficient welding work have to choose the welding methode to be suitable with site condition. This research will explain the differences of three welding methods consist of SMAW, FCAW and SAW weld methode based on strengthening and economic value. The strengthening of welding result are tested by dectructive test consist of tensile, bending and impact test. It carried out the calculation of weld cost per kgs, weld speed per meter and electrode consumption to know the differences of economic value for all that welding material. The test result showed that no differences of tensile strength between SMAW, FCAW and SAW welding methode, max. 1 %, but SMAW weld methode have yield strength 4 % better than FCAW weld methode and 14 % better than SAW weld methode. FCAW weld methode ductility value 34 % mare than SMAW weld methode and 37 % more than SAW weld methode. FCAW weld methode have economic value 67 % more than SMAW weld methode and 42 % more than SAW weld methode. SAW weld methode on horizontal weld position have speed 63 % more faster than FCAW weld methode and 72 % more faster than SMAW weld methode. SAW weld methode have electrode consumption 6 % more efficient than FCAW weld methode and 50 % more efficient than SMAW weld methode.